2016
DOI: 10.18632/oncotarget.13679
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin level trajectories in the early treatment period are related with survival outcomes in patients with breast cancer

Abstract: Hemoglobin (Hb) levels are reportedly related with treatment outcomes and survival in patients of breast cancer. However, the long-term change in Hb levels after treatment and the effects of Hb on survival remain unknown. This retrospective cohort study enrolled 1931 breast cancer patients with pathological stage I-IV between 1/1/2003 and 12/31/2013. Latent class modeling was used to identify trajectories in monthly Hb levels over time. The primary endpoint was 10-year cancer-related death. We identified 5 dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In this study, low hemoglobin levels at baseline were associated with reduced TTF. Moreover, previous studies associated the low hemoglobin levels including anemia with poor survival prognosis in breast cancer patients [ 25 28 ]. Thus, low hemoglobin levels may be a robust prognostic indicator for reduced TTF for breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, low hemoglobin levels at baseline were associated with reduced TTF. Moreover, previous studies associated the low hemoglobin levels including anemia with poor survival prognosis in breast cancer patients [ 25 28 ]. Thus, low hemoglobin levels may be a robust prognostic indicator for reduced TTF for breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In some cancers such as breast cancer and lung cancer, patients’ hemoglobin levels are related to treatment outcomes and survival. 13,14 In cervical cancer, anemia is associated with poor local disease control and a decreased survival rate. 15,16 Improving hemoglobin levels in patients with cervical cancer may help achieve better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin (Hb) levels had been reported by a number of studies to be associated with treatment outcomes and survival of patients of various cancer types (57)(58)(59) including breast cancer (60). It was reported that anemia in cancer patients is a prognostic factor associated with shorter survival (61).…”
Section: Hemoglobin Statusmentioning
confidence: 99%